Diversidade genética de quatro linhagens de Oreochromis niloticus utilizando o marcador RAPD - Massago, Haluko [UNESP]; Ribeiro, Ricardo Pereira; Barrero, Nelson Maurício Lopera; Povh, Jayme Aparecido; Castagnolli, Newton; Gomes, Patrícia Cristina (My University, 2009)
The aim of this study was to analyze the genetic diversity of four Nile Tilapia (Oreochromis niloticus) strains using the RAPD marker. Fin samples of GIFT (G), Chitralada (C), Supreme (S) and Bouaké (B) juvenile stocks have been collected. The 11 primers used yielded 81 fragments of which 41.98% were polymorphic. The percentage of polymorphic loci (G: 18.52%; C: 19.75%; S: 20.99% and B: 24.79%) showed that there was a genetic differentiation among the strains, showing the G st values a high (B×G: 0.231; B×C: 0.224; G×C: 0.194 and S×C: 0.208) and elevated (BxS: 0.315 and G×S: 0.270) differentiation. The highest gene flow (N m) was among the G×C (2.082) strains. The distance and genetic identity values (0.044 and 0.957 respectively) and the dendrogram indicate that the G×C is the most genetically similar strains. The genetic similarity was high among of the strains (G: 0,932; C: 0,903; S: 0,891 AND B: 0.900). These results will enable a correct reproductive and genetic strains management.
Genetic diversity of four Oreochromis niloticus strains using the RAPD marker
Keywords: Bouaké; Chitralada; Genetic variability; GIFT; Supreme; Tilapia